Interdisciplinary Insights for Digital Touch Communication - Jewitt, Carey (Human-Computer Interaction Series, 2020)
Communication is increasingly moving beyond 'ways of seeing' to 'ways of feeling'. This Open Access book provides social design insights and implications for HCI research and design exploring digitally mediated touch communication. It offers a socially orientated map to help navigate the complex social landscape of digitally mediated touch for communication: from everyday touch-screens, tangibles, wearables, haptics for virtual reality, to the tactile internet of skin. Drawing on literature reviews, new case-study vignettes, and exemplars of digital touch, the book examines the major social debates provoked by digital touch, and investigates social themes central to the communicative potential and societal consequences of digital touch: · Communication environments, capacities and practices · Norms associations and expectations · Presence, absence and connection · Social imaginaries of digital touch · Digital touch ethics and values The book concludes with a discussion of the significance of social understanding and methods in the context of Interdisciplinary collaborations to explore touch, towards the design of digital touch communication, 'ways of feeling', that are useable, appropriate, ethical and socially aware.